Systematic review on the impact of nursing actions on patients with breast cancer (Research, Society and Development, 2024)
The research emphasizes the importance of prevention, early detection and emotional support during and after treatment, demonstrating how nursing interventions can significantly improve treatment outcomes and patients' recovery. The study aims to carry out a systematic review on the impact of nursing actions on women with breast cancer. For this research, the systematic review method was used. The results indicate the need for an integrative and humanized approach, which transcends conventional medical treatments and encompasses emotional and psychological support, essential for the recovery and improvement of patients' quality of life. The study reinforces the need for health policies that encourage continuing education and professional development of nurses, aiming to improve care practices and expand the positive impact on breast cancer treatment. The conclusion highlights the transformative role of nursing in cancer care, highlighting the urgency of advances in health policies that value and effectively integrate these interventions.